PERAN MEDIA DIGITAL "GOOGLE SITES" DALAM LAYANAN BIMBINGAN KLASIKAL UNTUK MENINGKATKAN DISIPLIN DIRI PESERTA DIDIK - Syafa'atur Rohmah, Ida; Sudibyo, Hanung; Agung Nugraha, Rahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid development of digital technology has transformed educational practices, including guidance and counseling services in schools. This study aims to analyze the role of digital media Google Sites in classical guidance services to improve students' self-discipline. This research is motivated by the low level of students' self-discipline, characterized by tardiness, non-compliance with school rules, and low responsibility in completing academic tasks. A quasi-experimental approach with a one-group pretest–posttest design was employed. The subjects of this study were junior high school students who participated in classical guidance services using Google Sites as an interactive digital medium. Data were collected through self-discipline questionnaires, observation sheets, and documentation. The results show a significant improvement in students' self-discipline after the implementation of Google Sites-based classical guidance services. Indicators such as time management, rule compliance, learning responsibility, and self-control demonstrated notable increases. These findings indicate that Google Sites serves not only as an information delivery platform but also as an effective medium to foster students' self-regulation and reflective learning. Therefore, the integration of Google Sites in classical guidance services is recommended as an innovative and effective strategy to enhance students' self-discipline in secondary education. Keywords: Google Sites, Classical Guidance, Digital Media, Self-Discipline, Students